Analysis Of Age, Nutrition Status With Premenstrual Syndrome, And Health Education On The Knowledge Of Adolescents At Tri Guna Bhakti Junior High School, Surabaya - Siti Alfiah; Ani Media Harumi (Malahayati Nursing Journal, 2022)
ABSTRACT Women in their lives do not escape the existence of menstrual cycles that occur periodically and will feel disturbed if they experience a change. Disorders commonly experienced by women before menstruation is called premenstrual syndromeAnalyze the relationship between age at menarche, nutritional status with premenstrual syndrome and explain the effect of health education on adolescent knowledge This study uses quasi-experimental research with one group pretest and posttest-only design. The number of samples in the study was 50 respondents with a simple random sampling technique. This research was conducted at Tri Guna Bhakti Junior High School, Surabaya.Most respondents (62%) experienced menarche at the age of 12-14 years, most respondents also had normal nutritional status (50%). The incidence of Premenstrual Syndrome was experienced by most of the respondents (70%). The results of statistical tests showed that there was a relationship between nutritional status and the incidence of PMS, but there was no relationship between age and the incidence of PMS. Health education also influences students' knowledge about PMS There is no relationship between the age of menarche and the incidence of premenstrual syndrome, but on the contrary, there is a relationship between nutritional status and the incidence of premenstrual syndrome. The role of midwives in providing education and counseling about PMS to young women throughout the school is to increase knowledge about PMS and to improve diet, lifestyle, and physical activity (exercise) so that they can anticipate the occurrence of PMS and can compensate when experiencing PMS symptoms.. Keywords: Premenstrual Syndrome, Student, Nutritional Status, Age ABSTRAK Perempuan dalam kehidupannya tidak luput dari adanya siklus haid yang terjadi secara periodik, dan akan merasa terganggu bila mengalami suatu perubahan. Gangguan yang biasa dialami wanita sebelum menstruasi disebut sindrom pramenstruasi. Menganalisis hubungan usia menarche, status gizi dengan premenstrual syndrome serta mengetahui pengaruh pendidikan kesehatan terhadap pengetahuan remaja.Penelitian ini menggunakan penelitian quasi experiment dengan rancangan one grup prestest and postetst only. Jumlah sampel dalam penelitian sejumlah 50 responden dengan Teknik simple random sampling.Penelitian ini dilakukan di SMP Tri Guna Bhakti Kota Surabaya.Sebagian besar responden ( 62 %) mengalami menarche di usia 12-14 tahun, sebagian besar responden juga memiliki status gizi yang normal (50%). Kejadian Premenstrual Syndrome dialami oleh sebagian besar responden (70%). Hasil uji statistik menunjukkan bahwa terdapat hubungan antara status gizi dengan kejadian PMS, namun tidak terdapat hubungan antara usia dengan kejadian PMS. Pendidikan kesehatan juga memiliki pengaruh terhadap pengetahuan siswi tentang PMS.Tidak terdapat hubungan antara usia menarche dengan kejadian premenstrual syndrome, Namun sebaliknya, terdapat hubungan antara status gizi dengan kejadian premenstrual syndrome. Peran bidan dalam memberikan edukasi dan konseling tentang PMS kepada remaja putri di seluruh sekolah untuk meningkatkan pengetahuan tentang PMS dan dapat memperbaiki pola makan, gaya hidup dan aktivitas fisik (olahraga) agar dapat mengantisipasi terjadinya PMS dan dapat mengkompensasi saat mengalami gejala-gejala PMS. Kata Kunci: Premenstrual Syndrome, Siswi, Status Gizi, Usia